The Stability and Growth Pact Time to Rebuild! - Peter Bofinger; Eric Mayer (University of Würzburg, Department of Economics, 2004)
Within this paper we specify a symmetric two country model for the euro area to evaluate monetary and fiscal policy interaction with decentralized fiscal authorities. Obviously this calls for rules which neatly balance the chances and perils. Thereby we show that stringent rules are a prequisitive for a harmonious functioning of a monetary union. Nevertheless given the ability of fiscal policy to effectively stabilize the economic cycle we show that the current rules in reign are of little use. We close the paper by making some suggestions along which the Stability and Growth Pact might be reformed.
Keywords: E63; H6; F31; 330; Economic and Monetary Union; Fiscal Policy; Fiscal Rules; Stability and Growth Pact